Pengaruh Pendidikan Kesehatan terhadap Perilaku Orang Tua dalam Pencegahan Infeksi pada Anak dengan Kanker - PUSPITA, LUH MIRA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Background: Infection is the major cause of death in child cancer. Implementation of infection prevention can be implemented by applying handwashing, using antiseptic bath, oral care, visitor restrictions, application isolation, and use of barrier precautions. The problem faced is the lack of awareness and understanding of families on how to prevent infection. Intervention of health education showed effectiveness to increase awareness and promote health behavior. This research aimed to analyze the effect of health education on the behavior of parents in the prevention of infection in children with cancer. Methods: This research is the Pre Experimental with One Group Pretest-Posttest Design. The population in this study were all parents who have children with cancer are treated in a pediatric cancer ward Dr. Sardjito Hospital Yogyakarta. Sampling was performed by Consecitive Sampling with minimum sample size is 68 respondents. Analysis data using Paired Sampel t-Test for attitude and using Wilcoxon Test for knowledge and practices. The predictive value used was Î±=0,05 and CI= 95%. Results: The average score on knowledge, attitude, and practices before given health education was 75.75, 82.21, and 46.26. The average score after given health education was 90.69, 86.23, and 70.09. There was an increase in the average scores before and after health education. P-value in the variable knowledge, attitude, and practide of each of the 0.000 so that there are significant differences between before and after health education. Conclusions: There is the effect of health education on the behavior of parents in the prevention of infection in children with cancer.